2021
DOI: 10.1021/acs.oprd.1c00372
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Monitoring of Continuous Pharmaceutical Mixed Suspension Mixed Product Removal Crystallization Using Image Analysis

Abstract: In this work, we developed an in-line image analysis system for the monitoring of the continuous crystallization of an active pharmaceutical ingredient. Acetylsalicylic acid was crystallized in a mixed suspension mixed product removal crystallizer, which was equipped with overflow tubing as an outlet. A steep glass plate was placed under the outlet onto which the slurry dripped on its surface. The glass plate spread and guided the droplets toward the product collection filter. A high-speed process camera was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 56 publications
(103 reference statements)
0
4
0
Order By: Relevance
“…However, in most cases, the matrix complexity usually leads to side phenomena which make the use of specific techniques mandatory [55]. Moreover, conventional procedures require to perform several samplings at regular intervals followed by sample preparation and chromatographic separation steps [56,57]. Recently, ambient ionization mass spectrometry (AMS) has been successfully applied to monitor online and offline chemical reactions.…”
Section: On-line Monitoringmentioning
confidence: 99%
“…However, in most cases, the matrix complexity usually leads to side phenomena which make the use of specific techniques mandatory [55]. Moreover, conventional procedures require to perform several samplings at regular intervals followed by sample preparation and chromatographic separation steps [56,57]. Recently, ambient ionization mass spectrometry (AMS) has been successfully applied to monitor online and offline chemical reactions.…”
Section: On-line Monitoringmentioning
confidence: 99%
“…For both devices, the inline microscope showed that increasing the input power significantly reduced the induction time. Another inline image monitoring system known as dynamic image analysis (DIA) was developed for the continuous crystallization of acetylsalicylic acid [102]. This system was used for the first time in a continuous mixed suspension mixed product removal (MSMPR) crystallization process.…”
Section: Photo-optical Sensors and Image Analysismentioning
confidence: 99%
“…Continuous crystallization is a well-established research field with two basic operational implementations, which are the mixed suspension mixed product removal (MSMPR) crystallizers , and different tubular crystallizers (TC). The assembling of more MSMPR units into a cascade crystallizer system or the connection of different types of continuous crystallizers allows even more possibilities to control crystallization on its subprocess levels. The elevated performance of merging continuous and additive-controlled crystallization is demonstrated through the following examples from the literature.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 In addition, these benefits fit well with the idea of additive-controlled crystallization to simplify downstream formulation by targeted morphology alteration to make solid API production more efficient and economical. Continuous crystallization is a well-established research field with two basic operational implementations, which are the mixed suspension mixed product removal (MSMPR) crystallizers 27,28 and different tubular crystallizers (TC). 29−34 The assembling of more MSMPR units into a cascade crystallizer system 35 or the connection of different types of continuous crystallizers 36−40 allows even more possibilities to control crystallization on its subprocess levels.…”
Section: ■ Introductionmentioning
confidence: 99%